CDR 2019
DOI: 10.20517/cdr.2019.26
|View full text |Cite
|
Sign up to set email alerts
|

Cancer drug resistance: rationale for drug delivery systems and targeted inhibition of HSP90 family proteins

Abstract: Nanocarriers have been developed in order to protect drugs or to improve drugs efficiency by reaching the damaged tissue and avoiding systemic and local toxicity. By using Hsp90 inhibitors, some cancer drug resistances have been overcome and the loading into nanocarriers of such drugs has shown an increase of their activities. This review will present some advantages of Hsp90 inhibitors to treat resistant tumors; especially those targeting the mitochondrial protein TRAP1. We will also focus on the targeting of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 128 publications
0
3
0
Order By: Relevance
“…Cancer research has demonstrated that Hsp90 promotes malignant behaviors of cancer cells (Lacey and Lacey, 2021 ), such as uncontrolled proliferation, immune evasion, therapy resistance, and so on. Disruption of the chaperone mechanism of Hsp90 represents a potential method to inhibit tumor, as it can enhance the drug sensitivity of cancer cells (Li et al, 2019 ; Mathieu et al, 2019 ). Studies in fungi have demonstrated that elevated Hsp90 levels expedite the emergence of resistance to fungicides (Iyer et al, 2022 ), while reducing Hsp90 activity significantly increases the efficacy of fungicides (Fu et al, 2022 ; Li et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cancer research has demonstrated that Hsp90 promotes malignant behaviors of cancer cells (Lacey and Lacey, 2021 ), such as uncontrolled proliferation, immune evasion, therapy resistance, and so on. Disruption of the chaperone mechanism of Hsp90 represents a potential method to inhibit tumor, as it can enhance the drug sensitivity of cancer cells (Li et al, 2019 ; Mathieu et al, 2019 ). Studies in fungi have demonstrated that elevated Hsp90 levels expedite the emergence of resistance to fungicides (Iyer et al, 2022 ), while reducing Hsp90 activity significantly increases the efficacy of fungicides (Fu et al, 2022 ; Li et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The therapeutic efficacy of PTT is directly influenced by intracellular HSP expression levels, which have both protective and detrimental effects on cancer cells. Thus, the efficacy of hyperthermia therapy can be increased by inhibiting HSPs, which can reduce the thermal resistance of cancer cells and potentiate the cell-killing effect of hyperthermia [228]. Currently, HSP inhibitors are being used in combination with hyperthermia.…”
Section: Photothermal and Modulated Electro-hyperthermia Therapymentioning
confidence: 99%
“…To determine the susceptibility of RI and RII strains to QoIs, four fungicides were selected: trifloxystrobin (Tri), kresoxim-methyl (Kre), azoxystrobin (Azo), and pyraclostrobin (Pyr), which target the Qo site of the cytochrome bc1 complex. Additionally, seven other fungicides were selected to determine susceptibility: cyazofamid (Cya, targeted to the Qi site of the cytochrome bc1 complex), penthiopyrad (Pen, which targets the ubiquinone binding site), terbinafine (Ter, which inhibits lanosterol 14α-demethylase), fludioxonil (Flu, which is involved in the high-osmolarity glycerol (HOG) stress response signal transduction pathway), tolnaftate (Tol, which inhibits ergosterol production), difenoconazole (Dif, which inhibits fungal lanosterol-14α-demethylase activity and blocks ergosterol biosynthesis), and carbendazim (Car, which hinders microtubule assembly and disrupts spindle formation) [50][51][52][53][54][55]. Among them, Car was dissolved with 0.2 M HCL and the other fungicides were dissolved with DMSO.…”
Section: Sensitivity Test To Fungicidesmentioning
confidence: 99%